Determination of Egg Quality Characteristics Using Digital Image Analysis and Using Mathematical Formula in Guinea fowl (Numida meleagris) - Eleroğlu, Hasan (Turkish Journal of Agriculture - Food Science and Technology, 2021)
A total of 200 Guinea fowl (Numidae meleagris) eggs were obtained from guinea fowl flock at the age of 42 weeks of age, which are breeding at an altitude of 1240 m in the Wild Animals Breeding Station affiliated to Ministry of Forest and Water Affairs in Yozgat/Turkey. Eggs were taken at a resolution of 72 pixels per inch and 5184 × 3456 pixels in size, with the individual egg weights. Average Projection area (16,07 cm2), Perimeter (15,82 cm), Circularity (0,81), Height (5,17 cm), Width (4,04 cm), Mean grey value (82,82), Semi axis (2,02 cm), First long half height (2,96 cm), Second short half height (2,20 cm) values were determined by numerical image analysis. Mean Elongation (1,28), Shape Index (78,27) were calculated over the obtained data. Surface area (55,43 cm2), Height (5,16 cm), Width (3,77 cm), Elongation (1,37), Shape Index (73,01), Volume (40,14 cm3), Surface / Volume ratio (1,38), Shell weight (3,17 g), Shell thickness (0,28 mm), pore numbers (6666,25; 5132,39; 5011,12), pore density (120,32; 92,56; 90,31), Yellow ratio (14,85), Yellow Weight (5,95 g), Albumen Weight (30,75), Albumen ratio (77,21) parameters have been calculated using individual egg weights. Eggs were divided into 3 groups as <=70, 71-90, >90 in terms of gray value, eggs <=76, 77 – 79, >79 in terms of shape index, and <39, 39-43, >43 in terms of weight. The effects on the properties were investigated. As a result, it is thought that the data obtained can be used in scientific studies.